The Routledge Companion to Business History. - Wilson, John F. (Florence)
1 online resource (409 pages)
Keywords: "The Routledge Companion to Business History is a definitive work of reference, and authoritative, international source on business history. Compiled by leading scholars in the field, it offers both researchers and students an introduction and overview of current scholarship in this expanding discipline.?Drawing on a wealth of international contributions, this volume expands the field and explores how business history interacts theoretically and methodologically with other fields. It charts the origins and development of business history and its global reach from Latin America and Africa, to North America and Europe. With this multi-perspective approach, it illustrates the unique contribution of business history and its relationship with a range of other disciplines, from finance and banking to gender issues in corporations.?The Routledge Companion to Business History is a vital source of reference for students and researchers in the fields of business history, corporate governance and business ethics."--Provided by publisher